Radiation-Induced Skin Changes after Postmastectomy Radiation Therapy: A Pilot Study on Indicators for Timing of Delayed Breast Reconstruction - Kung, Theodore A.; Kidwell, Kelley M.; Speth, Kelly A.; Pang, Judy C.; Jagsi, Reshma; Newman, Lisa A.; Wilkins, Edwin G.; Momoh, Adeyiza O. (Journal of Reconstructive Microsurgery, 2019)
Background Delayed autologous breast reconstruction is commonly recommended in patients requiring postmastectomy radiation. This study examines gross and histologic changes in the breast skin of patients who have undergone postmastectomy radiation to help determine when radiation-induced skin changes begin to stabilize.Methods A prospective pilot study was conducted on eight patients with invasive breast cancer who required mastectomy and radiotherapy. At the time of mastectomy and 2, 4, 6, 8, and 12 months after completion of radiotherapy, a punch biopsy was taken from the radiated mastectomy skin of each patient. Serial standardized photographs were taken before and after radiotherapy to evaluate the degree of hyperpigmentation and graded by three blinded plastic surgeons. Skin biopsies were processed for histologic assessment of inflammation, elastin organization, and vascularity.Results Grading of patient photographs revealed an increase in hyperpigmentation after radiotherapy compared with baseline with a gradual improvement over time. SMAD3 immunostaining demonstrated a trend toward an increase in inflammation over 12 months. The elastin distribution within samples showed an increase in fiber disorganization, thickening, and clumping, with no improvement throughout the study period. The average number of vessels per high powered field decreased steadily through the duration of the study.Conclusion Histologic changes in dermal inflammation, elastin organization, and vascularity do not appear to correspond with the gradual improvement of hyperpigmentation, resulting from postmastectomy radiation. These histologic changes persist beyond the 12 month observation period and will require clinical correlation to determine the potential impact on postoperative outcomes.
Keywords: delayed breast reconstruction; postmastectomy radiation therapy; radiation skin changes